Amino-Claisen Rearrangements and Diels-Alder Reactions of Ketene N,O-Acetals: Reactivity Studies. On the Way to a Novel Tandem Process? - Neuschütz, Klaus; Simone, Jean-Mary; Thyrann, Thomas; Neier, Reinhard (My University, 2000)
We report the synthesis of N-benzyl-N-[(E)-buta-1,3-dienyl]propanamide (6) and its corresponding O-silyl-substituted ketene N,O-acetal 7 and their Diels-Alder reaction. Propanamide 6 reacted smoothly, whereas the yield obtained from 7 was low, probably due to polymerization of the dienophile induced by electron transfer. The ketene N,O-acetals 27a - g were synthesized starting from the corresponding benzamides 25a - e (Scheme 9). The ketene N,O-acetals 27a - g showed increased stabilities and underwent amino-Claisen rearrangements under thermal conditions. Using catalysts, interesting side reactions leading either to the annulated systems rac-35 - 37 or to a β-lactam rac-34 were observed.